Synowie w Synu. Naśladowanie Jezusa jako centralna idea chrześcijańskiej praxis - Szymik, Jerzy (Studia Pastoralne, 2026)
Christian existence is an implication of Christological orthodoxy and only in this light of the (Christological) truth it is of redemptive significance. Its shape depends on the answer to the question: who is Jesus, in essence? However, it is only possible to recognise Lord through our personal engagement, which is excellently expressed in the closeness to Him, contemplation and consent to His action. As an act of the whole existence, watching the Pierced (Crossed) leads us to recognize the truth about God in Christ, at the same time opening the way to imitate Him. The message of the Gospel is something more than a moral imperative; the obligation does not result here from individual conviction, but the reality – the taste and sense of life – has been changed irreversibly and redemptively.